PHYTOFABRICATION OF NANO-CRYSTALLINE PLATINUM PARTICLES BY LEAVES OF CERBERA MANGHAS AND ITS ANTIBACTERIAL EFFICACY. - F. AROCKIYA AARTHI RAJATHI; V.R.M. SUBRAMANYAM NAMBARU (International Journal of Pharma and Bio Sciences, 2014)
Biological synthesis of Platinum nanoparticles by leaves of Cerbera manghas extract through a green route was reported in this study. The properties of prepared nanoparticles were characterized by Fourier Transform Infrared Spectroscopy (FT-IR), Transmission Electron Microscopy (TEM), X-ray diffraction (XRD). The formation of Platinum nanoparticles was confirmed by the presence of an absorption peak at 263 nm using UV–visible spectrophotometer. TEM image revealed that most of the particles were in spherical shape with size ranging from 9.60 nm to 11.70 nm. The nanoparticles were crystalline in nature and it was confirmed by XRD pattern. From the FTIR measurements it was noticed that reduction has been carried out by carboxyl and alcoholic groups present in the leaves of C. manghas. Furthermore, biologically synthesized Platinum nanoparticles were found to be effective against selected bacterial pathogens.